The electrical conductivity of the nutritive solution modifies yield and quality of fruits of Physalis peruviana - Colli-Cortés, Paola Magdalena; Sandoval Villa, Manuel; Rodríguez-Mendoza, Nieves; Guerra Ramírez, Diana (Revista Mexicana de Ciencias Agrícolas, 2020)
The cape gooseberry (Physalis peruviana L.) is a nightshade susceptible to soil diseases, for this reason it is proposed to grow it in Mexico under greenhouse and hydroponics. It is necessary to determine its response to the electrical conductivity of the nutrient solution (EC), which is why plants were exposed to 1, 2 and 3 dS m-1. Sunlight is another factor that affects the quality of the fruits, for which fruits were harvested from inside and outside the plant canopy. The effect of fruit maturity was also determined. The fruits were determined weight, Brix, firmness and color (L, a and b). The EC, location in canopy and fruit maturity generated 12 treatments. The data were compared with a range mean test. Of the fruits, the EC of the nutritive solution affected the firmness and the Brix except the weight. The position of the fruits in the canopy did not affect these variables either. The maturity at harvest affected the quality of the fruits. The fruits harvested 30 days after commercial maturity lost weight and firmness, and increased Brix in more mature fruits. Fruit location and maturity did not affect fruit color.